Second-Hand Clothes: Inequalities between the Global North and the Global South - Sandoval Hernández, Efrén (Frontera Norte, 2019)
The literature on second-hand clothes links two sides of the same phenomenon. Overproduction and overconsumption of goods in the framework of an unequal global order, together with the active participation of various actors and social institutions in trade and consumption at the local level, explain the movement of second-hand clothes from countries in the North to countries in the South. Studies focused on the global aspect of the phenomenon are concerned with the impact of second-hand clothing trade on local textile industries (Frazer, 2008), and they assess whether such trade reproduces the marginalization of inhabitants in the poorest countries (Haggblade, 1990; Field, Barrett, Browne, & May, 1996) instead of favoring employment opportunities, consumption, or state income (Brooks, 2012). Other studies consider possible solutions (Mhango & Nhiem, 2005; Mackintosh, 2011).